2013
DOI: 10.1016/j.jpeds.2013.03.081
|View full text |Cite
|
Sign up to set email alerts
|

Histological Characteristics of the Fetal Inflammatory Response Associated with Neurodevelopmental Impairment and Death in Extremely Preterm Infants

Abstract: To test the hypothesis that increasing severity of the fetal inflammatory response would have a dose-dependent relationship with severe neurodevelopmental impairment (NDI) or death in extremely preterm infants. Study design We report 347 infants 23 to 28 weeks gestational age admitted to a tertiary neonatal intensive care unit between 2006 and 2008. The primary outcome was death or NDI at 18–22 month follow-up. Exposure status was defined by increasing stage of funisitis (stage 1: phlebitis; stage 2: arteriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 32 publications
3
60
0
Order By: Relevance
“…Our observations of decreased basal survival in neonatal pups may have relevance to the increased mortality observed in human preterm neonates exposed to chorioamnionitis (27). The observed trend toward decreased survival in LPS-exposed, SeV-infected weanling mice in our studies might yield a clue to the enhanced mortality of preterm infants with RSV (reviewed in ref.…”
Section: Maternal Inflammation Infant Immunitysupporting
confidence: 61%
See 1 more Smart Citation
“…Our observations of decreased basal survival in neonatal pups may have relevance to the increased mortality observed in human preterm neonates exposed to chorioamnionitis (27). The observed trend toward decreased survival in LPS-exposed, SeV-infected weanling mice in our studies might yield a clue to the enhanced mortality of preterm infants with RSV (reviewed in ref.…”
Section: Maternal Inflammation Infant Immunitysupporting
confidence: 61%
“…(28)). The possibility of an association between antenatal inflammation and RSV-related mortality in human infants is intriguing and merits investigation, particularly given the often-subclinical fetal inflammation in the preterm population (27).…”
Section: Maternal Inflammation Infant Immunitymentioning
confidence: 99%
“…[21] identified that fetuses with plasma IL-6 greater than 11 pg/mL had significantly higher rates of overall severe neonatal morbidity, as well as RDS and proven or suspected sepsis. Further studies have reported the significant relationship between umbilical arteritis/severe fetal inflammatory response and severe neonatal morbidity [22; 23]. Our findings are in agreement with the prior reports that the fetal inflammatory response is highly correlated with neonatal morbidity.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to the maternal inflammatory response, FIRS, defined as cord IL-6 >11 pg/mL, significantly increased the risk for hearing screen failure in the study cohort, and has been associated with adverse neonatal outcomes, particularly intraventricular haemorrhage and early onset sepsis 25. Increasing severity of fetal vasculitis was associated with severity of composite neurodevelopmental impairment/death at 18–22 months’ adjusted age in infants 23–28 weeks’ gestation 26. Neither prior study reported hearing outcomes.…”
Section: Discussionmentioning
confidence: 85%